2002
DOI: 10.1093/jn/132.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Phytoestrogens Is Associated with a Favorable Metabolic Cardiovascular Risk Profile in Postmenopausal U.S. Women: The Framingham Study

Abstract: Hypertension, central obesity and dyslipidemia are associated with high cardiovascular risk. Estrogen therapy in women has beneficial effects on some of these metabolic cardiovascular risk factors. It is not known whether dietary estrogens have similar effects, especially in Western populations. We studied the association between dietary phytoestrogen intake and metabolic cardiovascular risk factors in postmenopausal women. For this purpose, 939 postmenopausal women participating in the Framingham Offspring St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
115
4
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(128 citation statements)
references
References 54 publications
3
115
4
6
Order By: Relevance
“…Two studies in Asian populations did find a positive effect of phytoestrogen intake on total cholesterol and LDL but the levels of intake are several fold higher in the Asian population as compared to western populations. In western postmenopausal women some positive effects of dietary phytoestrogens on plasma lipids were reported [28]. Our results are not consistent with these findings, but confounding by unmeasured factors could have caused the discrepancy.…”
Section: Discussioncontrasting
confidence: 96%
“…Two studies in Asian populations did find a positive effect of phytoestrogen intake on total cholesterol and LDL but the levels of intake are several fold higher in the Asian population as compared to western populations. In western postmenopausal women some positive effects of dietary phytoestrogens on plasma lipids were reported [28]. Our results are not consistent with these findings, but confounding by unmeasured factors could have caused the discrepancy.…”
Section: Discussioncontrasting
confidence: 96%
“…Epidemiological studies (19,20) have indicated that there is no significant association between the standard western dietary intake of isoflavones (0.369 -0.770 mg/day) and the reduction of cardiovascular events or lipid levels in different cohorts of postmenopausal women over prolonged periods of time (4 -6 years). Our subjects received Ͼ150 times this amount, yet no significant changes were observed over a 3-month period.…”
Section: Discussionmentioning
confidence: 99%
“…Whole grains contain higher amounts of fiber, vitamin E, magnesium, antioxidants and phytoestrogens (Slavin et al, 1997), the protective effects of which against chronic disease risk have been shown by previous studies (Stampfer et al, 1993;Ma et al, 1995;Anderson and Hanna, 1999;de Kleijn et al, 2002). Despite dietary recommendations to increased intake of whole grains, little research has been conducted on the physiologic effects of a diet high in whole grains, such that only one study, conducted in the Framingham Offspring Cohort, reported the association of whole-grain intake with the metabolic syndrome (McKeown et al, 2004).…”
Section: Introductionmentioning
confidence: 99%